Volume 5: Turbo Expo 2002, Parts a and B 2002
DOI: 10.1115/gt2002-30361
|View full text |Cite
|
Sign up to set email alerts
|

Micro Air Injection and Its Unsteady Response in a Low-Speed Axial Compressor

Abstract: A new approach, steady micro air injection from the casing, is proposed to improve the stability of a three-stage low-speed axial compression system. Although the injection rate is designated to be only a few ten thousandth of the compressor flow rate, such an injection is able to trigger the unsteady response and thus lower the mass flow rate at stall for up to 5.83%. At the same time, it keeps the steady compressor characteristic with no injection unchanged. In order to verify that the compressor response is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 10 publications
3
27
0
Order By: Relevance
“…Nie et al [22] performed air injection upstream of the first rotor to control rotating stall in a three-stage axial flow compressor. They carried out a parametric study by varying injected mass flow, axial distance of the injector from the rotor leading edge, radial penetration of the injector, and injection skew angle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nie et al [22] performed air injection upstream of the first rotor to control rotating stall in a three-stage axial flow compressor. They carried out a parametric study by varying injected mass flow, axial distance of the injector from the rotor leading edge, radial penetration of the injector, and injection skew angle.…”
Section: Introductionmentioning
confidence: 99%
“…A parametric study has been carried out by varying the axial distance of the injector from the rotor leading edge, jet-to-free-stream velocity ratio, injection pitch and skew angles, and number of injectors. The range of these parameters was chosen on the basis of the past literature [21,22,32] as well as considering the geometric characteristics of the present axial flow fan. A pulsed injection study was also carried out to investigate the possibility of further improvement in stall margin.…”
Section: Introductionmentioning
confidence: 99%
“…Despite much efforts and achievements on mass injection upstream of the tip of axial compressor, several topics should still be very interesting. (1) For a low-speed compressor, experimental results showed that the injected flow of only 0.05% of the compressor main flow is able to lower the mass flow rate at stall for up to 5.8% [10]. However, the effectiveness of steady micro-air injection and its effects on the performance of a high-speed compressor need detailed examination.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above-mentioned argument, a new approach, steady microair injection, was proposed to improve the stability of a lowspeed axial-flow compressor in [10]. Despite much efforts and achievements on mass injection upstream of the tip of axial compressor, several topics should still be very interesting.…”
Section: Introductionmentioning
confidence: 99%
“…Suder et al [50] proposed a discrete tip injection technique, and Nie et al [51] and Lin et al [52] based their proposal on microair injection. Whilst requiring significant power to drive the associated control system actuation, these control techniques result in 5 to 10 per cent improvement in compressor stall margin.…”
Section: Active: Air Injectionmentioning
confidence: 99%